No effects of experimental warming but contrasting seasonal patterns for soil peptidase and glycosidase enzymes in a sub-arctic peat bog - Weedon, J.T.; Aerts, R.; Kowalchuk, G.A.; van Bodegom, P.M. (Biogeochemistry, 2014)
The nature of linkages between soil C and N cycling is important in the context of terrestrial ecosystem responses to global environmental change. Extracellular enzymes produced by soil microorganisms drive organic matter decomposition, and are considered sensitive indicators of soil responses to environmental variation. We investigated the response of eight hydrolytic soil enzymes (four peptidases and four glycosidases) to experimental warming in a long-term climate manipulation experiment in a sub-arctic peat bog, to determine to what extent the response of these two functional groups are similar. We found no significant effect of experimental spring and summer warming and/or winter snow addition on either the potential activity or the temperature sensitivity (of V